The Education of Dyslexic Children from Childhood to Young Adulthood - Shaywitz, Sally E.; Morris, Robin; Shaywitz, Bennett A. (Annual Review of Psychology, 2008)
The past two decades have witnessed an explosion in our understanding of dyslexia (or specific reading disability), the most common and most carefully studied of the learning disabilities. We first review the core concepts of dyslexia: its definition, prevalence, and developmental course. Next we examine the cognitive model of dyslexia, especially the phonological theory, and review empiric data suggesting genetic and neurobiological influences on the development of dyslexia. With the scientific underpinnings of dyslexia serving as a foundation, we turn our attention to evidence-based approaches to diagnosis and treatment, including interventions and accommodations. Teaching reading represents a major focus. We first review those reading interventions effective in early grades, and then review interventions for older students. To date the preponderance of intervention studies have focused on word-level reading; newer studies are beginning to examine reading interventions that have gone beyond word reading to affect reading fluency and reading comprehension. The article concludes with a discussion of the critical role of accommodations for dyslexic students and the recent neurobiological evidence supporting the need for such accommodations.
Keywords: accommodations; classification; learning disabilities; neuroimaging; reading intervention, dyslexia; reading remediation; specific reading disability